Fungsi Pengawasan DPRD Kabupaten Pasaman Barat Terhadap Pelaksanaan Tindak Lanjut Hasil Pemeriksaan Laporan Keuangan Oleh Badan Pemeriksa Keuangan - Theo Satria D; Khairani Khairani; Hengki Andora (Dinasti Research, 2023)
In carrying out its supervisory function, the DPRD in this case describes the BPK's findings according to its authority. It is important to complete follow-up actions on BPK audit results. In this research, the formulation of the problem is: 1) DPRD supervision of the follow-up to the results of the audit of the BPK's financial reports; 2) Further action on the results of the West Pasaman Regency DPRD's supervision of the results of the BPK's financial report audit; 3) urge not to follow up on the results of the audit of the BPK's financial reports. The research uses an empirical juridical approach, descriptive analytical in nature. Data was obtained from legal materials and interviews, then analyzed qualitatively. The results of this research are 1) DPRD supervision starts from the BPK submitting the Audit Results Report until there is a response and evidence of follow-up from the Inspectorate which is then reviewed by the BPK; 2) The follow-up to the results of the West Pasaman Regency DPRD's supervision of the 2020 BPK LHP found indications of losses from official travel expenses, which had been deposited in the Regional Treasury; 3) The DPRD Secretary provides written sanctions to officials regarding the discovery of losses in official travel expenses that do not correspond to actual conditions.